The effect of differential rearing conditions on the consumption of and operant responding for ethanol in the Indiana university selectively bred alcohol-preferring (p) and -non-preferring (np) rat lines - Deehan, Gerald A. JR. (Kansas State University, 2009)
Exposing rats to differential rearing conditions, during early post-weaning development, has been shown to produce changes in a number of behaviors displayed during adulthood. The purpose of the current study was to investigate whether rearing alcohol-preferring (P) and non-preferring (NP) rats in an environmental enrichment condition (EC), a social condition (SC), or an impoverished condition (IC) would differentially affect the consumption of and operant responding for 10% ethanol. In Experiment 1 rats were tested for both limited access and free access (two bottle choice between water and ethanol) consumption of 10% ethanol. For, Experiment 2 rats were trained to respond in an operant chamber for ethanol and then provided concurrent access to 10% ethanol (right lever) and water (left lever). After concurrent access, rats were required to respond over a gradually increasing fixed-ratio schedule for 10% ethanol and finally a progressive ratio schedule for 10% ethanol, 15% ethanol, and 10% sucrose. For Experiment 3 rats were trained to respond for 10% sucrose and then assessed for the maintenance of operant responding for 10% sucrose. The data from this series of experiments shows that EC P rats consumed, responded for, and preferred 10% ethanol significantly less than their IC P counterparts. Also, EC P rats did not significantly differ from NP rats during any aspect of testing for all experiments. Experiment 3 failed to reveal a significant effect of rearing although there was a line effect that has been previously observed in the literature. Thus, it would appear from these results that rearing in an EC condition acts to protect alcohol-preferring rats from increased levels of consumption of, preference for, and responding for ethanol compared to rearing in an impoverished environment.
Keywords: Environmental Enrichment; Impoverished Environment; Alcohol Preferring (P) Rat; Alcohol Non-Preferring (NP) Rat; Ethanol Consumption; Ethanol Responding; Psychology, Experimental (0623); Psychology, Psychobiology (0349)